DFT Study of Zn-Modified SnP3: A H2S Gas Sensor with Superior Sensitivity, Selectivity, and Fast Recovery Time - Lijie Li (Nanomaterials, 2023)
The adsorption properties of Cu, Ag, Zn, and Cd-modified SnP3 monolayers for H2S have been studied using density functional theory (DFT). Based on phonon spectrum calculations, a structurally stable intrinsic SnP3 monolayer was obtained, based on which four metal-modified SnP3 monolayers were constructed, and the band gaps of the modified SnP3 monolayers were significantly reduced. The adsorption capacity of Cu, Zn-modified SnP3 was better than that of Ag, Cd-modified SnP3. The adsorption energies of Cu-modified SnP3 and Zn-modified SnP3 for H2S were −0.749 eV and −0.639 eV, respectively. In addition, Cu-modified SnP3 exhibited chemisorption for H2S, while Zn-modified SnP3 exhibited strong physisorption, indicating that it can be used as a sensor substrate. Co-adsorption studies showed that ambient gases such as N2, O2, and H2O had little effect on H2S. The band gap change rate of Zn-modified SnP3 after adsorption of H2S was as high as −28.52%. Recovery time studies based on Zn-modified SnP3 showed that the desorption time of H2S was 0.064 s at 298 K. Therefore, Zn-modified SnP3 can be used as a promising sensor substrate for H2S due to its good selectivity, sensitivity, and fast recovery time.